Construction of mechanically strong and dual network-induced elastomeric materials with self-healing functionality. (27th October 2022) - Gupta, Akash; S, Aiswarya; Basu, Debdipta; Banerjee, Shib Shankar
Abstract: Imparting contradictory features like mechanical robustness and self-healing capability in an elastomer is pretty tough. In this work, introduction of zinc dimethacrylate (ZDMA) onto macromolecular chains via ring-opening reaction and interaction between epoxy and ZDMA, a mechanically robust and dual network-induced elastomeric material with self-healing functionality was constructed in a commercially available and widely used epoxidized natural rubber (ENR). Self-adjustment of ionic moieties post deformation due to strong ionic interaction in the network along with the interdiffusion characteristics of ENR chains helps to achieve self-healing functionality. With increasing ZDMA loading, both the covalent and ionic networks increases. Surprisingly, ZDMA not only enhances self-healing ability by enhancing ionic interaction with ENR, but also enhances mechanical performance substantially by creating reinforcing effects owing to formation of ionic clusters as evident from the high-resolution transmission electron microscopy images. At 40 phr loading of ZDMA, the tensile strength and modulus at 100% elongation reached ∼14.0 and ∼3.2 MPa respectively, which were much higher than the conventional sulphur vulcanizate ENR. This work provides a facile strategy to develop a mechanically robust and self-healing elastomeric engineered materials using a widely important commercial rubber. Graphical abstract: Image 1 Highlights: A new kind of mechanically strong and dual networks elastomeric materials with self-healing functionality was developed. The developed materials showed high tensile strength (∼14.0 MPa) and 100% modulus (∼3.2 MPa). In-situ developed ionic clusters in the rubber matrix acts as a reinforcement.